The use of test tube plantlets for the assessment of Potato virus Y transmission by Myzus persicae and Aphis glycines - Nie, Xianzhou; Giguère, Marie-Andrée; Pelletier, Yvan (Phytoprotection, 2010)
Test tube plantlets were used to assess the transmission efficiency of Potato virus Y (PVY) from and to potato plants by the potato colonizing species green peach aphid (Myzus persicae) and the non-potato colonizing species soybean aphid (Aphis glycines). Similar levels of transmission of PVY by M. persicae were observed in the test tube plantlets and potted plants, demonstrating the reliability of this test for PVY transmission efficiency assay for aphids. The assay was then used to assess the transmission of PVYO and PVYN:O by M. persicae and A. glycines with two virus acquisition regimes, one with 5-min continuous probing and the other with 1-h acquisition access. The M. persicae mediated-transmission rate was 24.1% and 51.7% for PVYO and PVYN:O, respectively, under the 5-min acquisition regime; under the same acquisition regime, A. glycines led to 0.0% and 1.7% infection rates for PVYO and PVYN:O, respectively. Under the 1-h acquisition regime, no infection was observed except for PVYN:O by M. persicae, which exhibited an infection rate of 3.4%.